Welfare state-based agricultural policies in Malaysia - Khoirul Hidayah; Mohd Halim Mahphoth; Syabbul Bachri; Ramadhita (Cogent Social Sciences)
Food security has become a global issue for the Food Agriculture Organization. A country plays an active role in actualizing food sustainability. The concept of a welfare state requires a country to be competent in realizing people’s prosperity. The discussion of Malaysian agricultural policies for objectifying the welfare state has drawn attention because it strengthens food security. This study is based on empirical research that uses a descriptive qualitative approach. The primary data are from interviews with the Federal Agricultural Marketing Authority (FAMA) officials and the secondary data are from Malaysian policy documentation. These were then analyzed qualitatively using the welfare state theory. The article shows that Malaysia made agricultural policies comprehensively by strengthening regulations, funding, and supervising to morally support farmers, so they were motivated to advance the economic sector voluntarily. Malaysian agricultural policies to help farmers actualize the state’s dream of becoming a welfare state. The Malaysian government’s involvement in providing a supervising program, funding, and legal certainty regarding crops’ basic prices became a transformational power of the agricultural sector. The success of the Malaysian agricultural sector is a valuable lesson for the independent economy and food security reinforcement of others, specifically in Southeast Asia, which has similar geographic characteristics.